Harnessing the Unique Features of 2D Materials toward Dendrite‐free Metal Anodes. Issue 1 (17th March 2021) - Cao, Zhenjiang; Zhang, Yongzheng; Cui, Yanglansen; Gu, Jianan; Du, Zhiguo; Shi, Yongzheng; Shen, Kai; Chen, Hao; Li, Bin; Yang, Shubin
Abstract : Electrochemically active metal anodes, such as lithium, sodium, potassium, and zinc, have attracted great research interests in the advanced rechargeable batteries owing to their superior theoretical energy densities. Unfortunately, the metal anodes suffer from the huge volume changes with loss of active materials during the plating and stripping processes, resulting in fast capacity decay. Moreover, the random growth of dendrites on the metal anodes will penetrate the separator, causing severe safety issues. Engineering metal anodes by introducing the 2D materials are widely investigated to alleviate these issues. Benefitting from the ultrathin structure feature and unique electrical properties, 2D materials are regarded as one of the best host of metal anodes. Besides, the tunable active sites on basal plane enable 2D materials to achieve favorable interaction with metal anodes. Moreover, some 2D materials exhibit good mechanical strength and flexibility, serving as building block for the artificial solid electrolyte interphase. In this review, we mainly disclosed the correlations between the intrinsic properties of 2D materials and their functions in guiding uniform nucleation, controlling the growth of metals, and accommodating the volume change. Also, the challenges of 2D materials in metal anodes are well discussed. Finally, the future directions to develop high‐performance metal anodes by taking advantage of these unique features of 2D materials are proposed. Abstract : In this review, the correlations between the intrinsic properties of 2D materials and their functions in guiding uniform nucleation, controlling the growth of metals, and accommodating the volume change were mainly disclosed. Also, the challenges of 2D materials in metal anodes are well discussed. Finally, the future directions to develop high‐performance metal anodes by taking advantage of these unique features of 2D materials are proposed.